Case report: A rare case of coexisting Waldenstrom Macroglobulinemia and B-cell acute lymphoblastic leukemia with KMT2D and MECOM mutations - Wang, Lingling; Tang, Jiao; Feng, Jun; Huang, Yongfen; Cheng, Yuexin; Xu, Hao; Miao, Yuqing (Frontiers in Immunology, 2022)
Background: Waldenstrom Macroglobulinemia (WM) is a rare and indolent lymphoma of B-cell origin characterized by elevated monoclonal IgM, with MYD88L265P mutation and CXCR4 mutation as common molecular alterations. B-cell Acute Lymphoblastic Leukemia (B-ALL) is clinically heterogeneous, characterized by abnormal proliferation and aggregation of immature lymphocytes in the bone marrow and lymphoid tissue. WM and ALL are hematologic malignancies of B-cell origin with completely different clinical manifestations and biological features. KMT2D and MECOM mutations are very rare in ALL and usually indicate poor disease prognosis. The coexistence of WM and ALL with KMT2D and MECOM mutations have not been reported. Case presentation: A 74-year-old female patient was diagnosed with WM in July 2018 and received four cycles of chemotherapy of bortezomib and dexamethasone. In November 2018, she received immunomodulator thalidomide as maintenance therapy. In November 2020, Bruton's Tyrosine Kinase inhibitors (BTKi) has been introduced into the Chinese market and she took zanubrutinib orally at a dose of 80 mg per day. The disease remained in remission. In December 2021, she presented with multiple enlarged lymph nodes throughout the body. Bone marrow and next-generation sequencing (NGS) suggested the coexistence of WM and B-ALL with KMT2D and MECOM mutations. The patient was treated with zanubrutinib in combination with vincristine and methylprednisolone, after which she developed severe myelosuppression and septicemia. The patient finally got remission. Due to the patient's age and poor status, she refused intravenous chemotherapy and is currently treated with zanubrutinib. Conclusions: The coexistence of WM and B-ALL is very rare and has not been reported. The presence of both KMT2D and MECOM mutations predicts a poor prognosis and the possibility of insensitivity to conventional treatment options. BTKi achieves its anti-tumor effects by inhibiting BTK activation and blocking a series of malignant transformations in B-cell tumors. In addition, it also acts on T-cell immunity and tumor microenvironment. Combination therapy based on BTKi may improve the prognosis of this patient.